Reconstruction Algorithms for Bistatic Radar and Ultrasound Imaging. - Levinson, Howard W. (Tufts Archival Research Center, 2005)
This research examines two different models of reconstruction technologies, one based on radar and the other on ultrasound. Both studied models are examples of bistatic reconstruction methods. in general there does not exist an inversion algorithm for bistatic reconstructions. The beginning f an inversion algorithm exists for the circular ultrasound model, but no such algorithm has been developed yet for the linear radar model. Furthermore, limited data problems (which we will be considering) are without inversion algorithms as well. Therefore, in this research we will be attempting to use an easily implemented algorithm to reconstruct functions. It turns out that this simple algorithm does indeed show most of the singularities of a function, and an ensuing discussion of microlocal analysis will provide mathematical reasonings for why this simple algorithm is able to reconstruct functions for bistatic imaging.